Temporal Evolution of Inflammation and Neurodegeneration With Alpha-Synuclein Propagation in Parkinson's Disease Mouse Model - Lai, Thuy Thi; Kim, Yun Joong; Nguyen, Phuong Thi; Koh, Young Ho; Nguyen, Tinh Thi; Ma, Hyeo-il; Kim, Young Eun (Frontiers in Integrative Neuroscience, 2021)
Alpha-synuclein (αSyn) propagation has been suggested to play a key role in the pathomechanism of Parkinson’s disease (PD) from many studies, but neurodegeneration and the involvement of inflammation in its pathologic progression are not well understood with regard to temporal relationship. In this study, by means of PD mouse model injected with intrastriatal αSyn preformed fibril (PFF), the temporal evolution of αSyn propagation, inflammation, and neurodegeneration was explored in the perspective of the striatum and the whole brain. In the PFF-injected striatum, inflammatory responses including the microglia and astrocyte were activated at the earliest stage and reduced with time, and the phosphorylated form of αSyn accumulation increased behind it. Thereafter, the degeneration of striatal dopaminergic neurons became significant with the conspicuity of behavior phenotype. Similar pattern of forefront eruption of inflammation and following αSyn propagation was noted in the opposite striatum, which was not injured by PFF injection. In analyzing the whole brain, inflammatory responses were activated at the earliest stage, and the soluble αSyn expression increased concurrently. Inflammatory response decreased afterward, and the accumulation of the insoluble form of αSyn increased behind it. Our results suggested that the inflammatory response may precede the accumulation of the pathologic form of αSyn; thereafter, the neurodegeneration and motor dysfunction followed αSyn proliferation in the PD mouse model. From this model, recognizing the temporal relationship between inflammation, αSyn propagation, and neurodegeneration may be helpful in establishing PD animal model and monitoring the effect of interventional therapy.